International WIL placements: Their influence on student professional development, personal growth and cultural competence - Gribble, Nigel; Dender, Alma; Lawrence, Emma; Manning, Kirrily; Falkmer, Torbjorn (Asia-Pacific Journal of Cooperative Education, 2014)
In the increasingly global world, skills in cultural competence now form part of the minimum standards of practice required for allied health professionals. During an international work-integrated learning (WIL) placement, allied health students' cultural competence is expected to be enhanced. The present study scrutinized reflective journals of students who completed an international WIL placement to identify themes related to student learning. A retrospective content analysis identified three core themes with sub-themes: Cultural Competence with three subthemes: cultural egocentricity and cultural adjustment, cultural conflict in dealing with disability (not resolved over time) and, communication and language barriers; Professional Development with two subthemes: the evolution of evaluating success and impact on future practice, and Personal Growth with two subthemes: newfound reality - constant self-discovery and social responsibility. These themes provide guidance for academics in preparing students beforehand and the reflections during international WIL placements.